The synergistic effect of transport distance and season on poultry mortality during transport to slaughterhouses - Justova, Eva; Vecerek, Vladimir; Semerad, Zbynek; Vucinic, Marijana; Valkova, Lenka; Voslarova, Eva (Poultry science, 2025)
This study investigated the combined effects of transport distance and season on poultry mortality rates (end-of-lay hens, broiler chickens, turkeys, and ducks) during transport to slaughterhouses. Retrospective data analysis included all poultry shipments from Czech farms to Czech slaughterhouses from 2017 to 2023. In total, 11,503,789 end-of-lay hens, 807,874,546 broiler chickens, 1,075,070 turkeys, and 28,012,184 ducks were transported in the monitored period. The highest mortality rates were observed in laying hens (1.212 %) and broiler chickens (0.884 %) during winter when transported over very long distances (301 km and more). For ducks, peak mortality (0.589 %) was found during summer transport over the distances of 201-300 km (no ducks were transported for longer distances). In turkeys, the highest mortality (0.598 %) was recorded in autumn over distances of 51-100 km, likely due to the limited number of birds transported over longer distances (97 % of turkeys transported within 100 km) and during extreme-temperature seasons. These findings highlight the need for species-specific transport management strategies, particularly for vulnerable categories such as end-of-lay hens and broiler chickens.
Keywords: DOA; Turkey; Hen; Broiler; Duck